Structural and Functional Model of Training Language and Literature Teachers on the Principles of Praxeology - Lyudmyla Romanovska (Pedagogical Discourse, 2025)
The article examines the theoretical foundations and practical significance of applying a praxeological approach to the professional training of future language and literature teachers. Modern philological education faces several challenges, including the imbalance between theoretical and practical preparation, insufficient integration of key professional competencies, and the need to align teacher training with the demands of contemporary school education. Praxeology, understood as a science of effective and rational activity, offers a methodological framework that enables the optimization of pedagogical actions, the development of reflective skills, and the formation of an ability to plan, organize, and evaluate professional performance.Based on an analysis of scientific research, the article outlines the methodological, organizational, and evaluative functions of the praxeological approach in teacher education. A structural-functional model of training is proposed, integrating five interrelated components: target, content, operational-technological, communicative, and reflective-evaluative. The model incorporates key principles of praxeology – goal-orientedness, effectiveness, rationality, systemness, reflexivity, and adaptability – and a system of content modules that ensure the coherence of theoretical knowledge, pedagogical practice, research activities, and self-development.The study also identifies pedagogical conditions necessary for implementing the model, including the integration of theory and practice, the use of digital technologies, project-based and research-oriented learning, reflective practices, and mentor support. The proposed model enhances the readiness of future teachers to perform professional tasks effectively and supports their development as competent, reflective, and innovative educators. Its implementation contributes to increasing the overall quality of philological education and ensures its alignment with contemporary educational standards. The results of the study may serve as a methodological basis for further improvement of teacher training programs within higher education institutions.